2020
DOI: 10.3390/rs12203468
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling Household Survey Data Using Remote Sensing to Map Socioeconomic Groups in Kampala, Uganda

Abstract: Sub-Saharan African cities are expanding horizontally, demonstrating spatial patterns of urban sprawl and socioeconomic segregation. An important research gap around the geographies of urban populations is that city-wide analyses mask local socioeconomic inequalities. This research focuses on those inequalities by identifying the spatial settlement patterns of socioeconomic groups within the Greater Kampala Metropolitan Area (Uganda). Findings are based on a novel dataset, an extensive household survey with 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Fig. 2 shows the result of their remote sensing analysis showing what housing types define the city layout 1 in Kampala (Hemerijckx et al 2020). The present study analyses food accessibility and insecurity of urban dwellers through the lens of these four SECs.…”
Section: Study Area: the Greater Kampala Metropolitan Areamentioning
confidence: 95%
See 2 more Smart Citations
“…Fig. 2 shows the result of their remote sensing analysis showing what housing types define the city layout 1 in Kampala (Hemerijckx et al 2020). The present study analyses food accessibility and insecurity of urban dwellers through the lens of these four SECs.…”
Section: Study Area: the Greater Kampala Metropolitan Areamentioning
confidence: 95%
“…For these reasons, the GKMA can be considered an illustrative case for rapidly changing SSA cities. In the GKMA, inhabitants of a higher socioeconomic position mainly reside on hilltops while low-lying wetland areas are dominated by slum housing (Hemerijckx et al 2020;Vermeiren et al 2016). Hemerijckx et al (2020) have defined four socioeconomic clusters (SECs) in Kampala based on migration status and income.…”
Section: Study Area: the Greater Kampala Metropolitan Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, food flow maps were prepared to identify the outlet in the area, which could be linked to other initiatives that link the food acquisition to the origin of the food. Moreover, there seem to be incentives to continue the intervention even after the NOURICITY project will finish, and the approach could be transferred to neighbouring and other parishes within Kampala using the information of other studies, such as Hemerijckx et al (2020), which include Kanyanya in their research as well.…”
Section: Boundaries Of the Food Systemmentioning
confidence: 99%
“…Such fast and uncontrolled urban growth can lead to a very heterogeneous urban landscape with wealthy districts characterized by modern houses, big green gardens and asphalted roads, but also with informal Jonas Van de Walle jonas.vandewalle@kuleuven.be Extended author information available on the last page of the article. settlements usually composed of densely built shacks made of corrugated metal sheets that are only accessible via small murrum alleys, typical unpaved but tamped roads (Vermeiren et al 2012;Hemerijckx et al 2020). In an observational study, Scott et al (2017) demonstrated that such heterogeneous urban landscape results in intra-urban temperature variations in the city of Nairobi, Kenya, highlighting the presence of hotter air in informal settlements and suggesting heterogeneous hazards and vulnerability to urban heat in Sub-Saharan African cities.…”
Section: Introductionmentioning
confidence: 99%